2017
DOI: 10.1111/dme.13398
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pregnancy planning on maternal and neonatal outcomes in women with Type 1 diabetes

Abstract: AimsTo assess the effect of pregnancy planning on maternal and neonatal outcomes in women with Type 1 diabetes.MethodsPregnancy planning was assessed retrospectively in a cohort of women who participated in the Diabetes and Pre‐eclampsia Intervention Trial (DAPIT). Pregnancy planning was determined based on self‐report as to whether pregnancy was planned or unplanned. The effect of pregnancy planning on maternal and neonatal outcomes was examined, controlling for confounding variables.ResultsA total of 747 wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…Pre‐pregnancy counseling results in better metabolic control at conception and has been linked to better outcomes for women with type 1 and type 2 diabetes: higher rates of stillbirth and preterm delivery have been reported among women who booked late . Mean HbA1c was almost 1% lower in a British cohort than in the present study, which also demonstrated higher rates of congenital anomalies, highlighting the relevance of preconception care.…”
Section: Discussionmentioning
confidence: 40%
See 1 more Smart Citation
“…Pre‐pregnancy counseling results in better metabolic control at conception and has been linked to better outcomes for women with type 1 and type 2 diabetes: higher rates of stillbirth and preterm delivery have been reported among women who booked late . Mean HbA1c was almost 1% lower in a British cohort than in the present study, which also demonstrated higher rates of congenital anomalies, highlighting the relevance of preconception care.…”
Section: Discussionmentioning
confidence: 40%
“…Pre-pregnancy counseling results in better metabolic control at conception and has been linked to better outcomes for women with type 1 23 and type 2 diabetes: higher rates of stillbirth and preterm delivery have been reported among women who booked late. 24…”
Section: Discussionmentioning
confidence: 99%
“…Type 2 DM is increasingly recognised as an important risk factor for poor pregnancy outcomes and is becoming more common. Diabetes type for women giving birth between 2007 and 2017 was type 2 for 12 787 participant women and type 1 for 23 664 participant women; thus, more than one in three women had type 2 DM . The comparable numbers of participant women with type 1 and type 2 DM were 15 407 and 1662 for publications about births between 1987 and 2006; thus in this earlier era, fewer than one in ten women with diabetes were reported as having type 2 .…”
Section: Resultsmentioning
confidence: 95%
“…Pre pregnancy care has been variably defined by asking women if the pregnancy was planned, whether they had consulted a general or specialist health practitioner or achieved other aspects of optimal preparation . The majority of papers included HbA1c as a measure of preconception glycaemic control . Others relied on clinical notes about the purpose of outpatient consultations or whether a pregnancy was planned .…”
Section: Resultsmentioning
confidence: 99%
“…Wotherspoon et al 49 , em 2017, em análise retrospectiva de dados de 747 pacientes do Diabetes and Pre-eclampsia Intervention Trial, descrevem a importância da avaliação pré-concepcional. No Reino Unido, 39% das participantes daquele estudo tinham gestações não planejadas e tal condição, comparada às pacientes com avaliação pré-concepcional, se associou à maior frequência de fetos com peso menor que percentil 5 (9% x 3%, p=0,004),internação do recém-nascido em unidade de terapia intensiva (64% x 50%, p=0,001) e níveis mais elevados de HbA1C durante todo o pré-natal (HbA1C inicio do pré natal -8,9% x 7,7%, P<0,005).…”
Section: Segundo Trimestreunclassified